Accountability of the Implementing Online New Student Admission Program (PPDB Online) in North Sumatra Province - Hasibuan, Yanisah; Ginting, Simson; Sihombing, Tunggul (Musamus Journal of Public Administration, 2024)
This research is based on the problem of implementing PPDB online which is not running responsibly. The implementation of the PPDB is accounted for by the North Sumatra Provincial Education Office which is the locus of the research. This research uses qualitative research methods to describe the accountability of online PPDB implementation in North Sumatra Province. The data collection process is through interviews, documentation, observation, and relevant literature studies and is presented through data reduction techniques, data presentation, data interpretation, and concluding. The research results are described through Ellwood's theory which suggests that public accountability consists of honesty accountability, legal accountability, and process accountability. The research results describe that accountability for program implementation is not going well. Illustrated through the accountability aspect of honesty, namely the attitude of implementers who are not honest and open to the user community. The legal accountability aspect is that program implementation does not run according to the schedule specified in the applicable regulations, and the process aspect is that program implementation does not run in an orderly manner due to facilities or information systems that do not function well in accommodating or supporting the PPDB activity process.